Rent Regulation in Portugal - Alves, Sónia (2023)
The regulation has a significant impact on tenant–landlord relations and the overall functioning of the private rented sector. Different forms of rent regulation—in relation to rent levels, rent increases, security of tenure, etc.—also affect the quality, the social composition and, ultimately, the size of the private rented sector. Together they affect the character of much urban regeneration and renewal. The introduction in Portugal of more flexible rent regimes that aimed to gradually replace open-ended tenancies with freely negotiated contracts led researchers to classify the country as a free market system.